2004
DOI: 10.1111/j.1440-1835.2004.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

New genus Koliellopsis (Trebouxiophyceae, Chlorophyta): its phylogenetic position inferred from ultrastructure and nuclear ribosomal DNA sequences

Abstract: Koliellopsis inundata Lokhorst gen. & sp. nov. (Trebouxiophyceae) is described from periodically flooded agricultural fields in the borderland of Belgium and the Netherlands. This new, unbranched, filamentous alga is typified by relatively long vegetative cells, which have a bilobed, laminate chloroplast with a nucleus positioned in its median constriction. Its filaments lack a distinct basal-distal differentiation and both ends terminate in about equally shaped, rounded or, more often (slightly) tapering cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…2006, this paper). The variation in habit (e.g., filaments and unicells) is similar to groups being discovered in the Chlorophyta where habit and other characters are not good predictors of relationships (Lokhorst et al. 2004).…”
Section: Discussionsupporting
confidence: 68%
“…2006, this paper). The variation in habit (e.g., filaments and unicells) is similar to groups being discovered in the Chlorophyta where habit and other characters are not good predictors of relationships (Lokhorst et al. 2004).…”
Section: Discussionsupporting
confidence: 68%
“…Neustupa et al (2007) also reported that the Stichococcus jenerensis CAUP J 1302 strain grows mostly as unicells or twocelled short filaments, and longer filaments comprising 4 to 10 (rarely 20) cells were regularly observed on agar solidified BBM (Bold s Basal Medium). Recently, analyses of 18S rRNA sequences indicated that Stichococcus belongs to the Trebouxiophyceae (Friedl and O Kelly 2002, Karsten et al 2005, Katana et al 2001, Lokhorst et al 2004. Moreover, Karsten et al (2005) showed that the genus Stichococcus is a member of the Prasiola Meneghini clade in the 18S rRNA tree.…”
Section: Discussionmentioning
confidence: 99%